PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GAMIFIKASI BERMUATAN KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI PUISI SISWA - Fawwaz Khalifa; Bagas Kurnianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low level of students' poetry comprehension may be attributed to the limited use of engaging learning media. This study aims to develop interactive learning media based on gamification incorporating local wisdom to improve students' ability to understand poetry. The research employed a Research and Development (RnD) method using the ADDIE development model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The study involved fourth-grade students of SD Negeri Ngaliyan 05 Semarang as the research subjects. Data collection techniques included interviews, observations, documentation, written tests, and questionnaires. The data were analyzed using normality tests, T-tests, and N-gain tests. The findings showed that the interactive learning media based on gamification and infused with local wisdom were rated as